Development of Science Learning Media Monsains (Science Monopoly) In Human Ingestion System Materials For Elementary School - Evi Rusmiaty; Helmia Tasti Adri; Annisa Mawardini (Universitas Djuanda, 2020)
This study aims to develop MONSAINS (Monopoly Science) learning media that is suitable for science learning materials for the fifth grade human digestive system. . The objectives of this study are: (1) To explain the steps for developing the Monopoly Science (MONSAINS) media on the material of the fifth grade human digestive system, (2) to determine the feasibility of developing the Monopolymedia Science (MONSAINS) on the material of the human digestive system in class V SD 3) Adding innovation in the development of learning media. This research is a type of research and development Research and Development (R n D) which is adevelopment model Borg and Gall with 7 stages taken. The media development stages carried out are: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product testing, (7) product revision . The test subjects were class V MI Pondok Leungsir in the 2020/2021 school year. The instrument used in this study was a validation questionnaire for material experts, media experts, teachers and students. The data analysis used was technical descriptive quantitative analysis. The number of subject trials is limited to only 5 students. The results of the validation that have been carried out obtain a very good category assessment from a scale of 5, the total score is obtained from an average score of 4.0 from material / content experts, an average score of 4.6 by design / media experts, an average score of 4.9 by a class V teacher at MI Pondok Leungsir. In addition, this product also obtained a very good score from an average score of 4.6 on a scale of 5, so it is considered the media to be very interesting and suitable for use by students in the teaching and learning process.